2023
DOI: 10.3390/cancers15020518
|View full text |Cite
|
Sign up to set email alerts
|

Ultrasound-Guided Percutaneous Thermal Ablation of Renal Cancers—In Search for the Ideal Tumour

Abstract: Over the recent years, the progress in imaging techniques has led to an increased detection of kidney tumours, including small renal masses. While surgery is still the standard of care, there is a growing interest in minimally invasive methods. Ultrasound (US)-guided percutaneous ablation is particularly attractive because it is a safe and relatively simple procedure. In this study, we investigated the success of percutaneous radiofrequency ablation (RFA) in relation to kidney tumour diameter and location. Bet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
13
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(13 citation statements)
references
References 36 publications
0
13
0
Order By: Relevance
“…Notably, the technical e ciency of US-induced RFA for T1a RCC treatment was only 75.4%, as reported by Jasinski et al 27 . In the RFA group, the high technical success and technique e cacy may be attributable to four reasons.…”
Section: Discussionmentioning
confidence: 57%
See 2 more Smart Citations
“…Notably, the technical e ciency of US-induced RFA for T1a RCC treatment was only 75.4%, as reported by Jasinski et al 27 . In the RFA group, the high technical success and technique e cacy may be attributable to four reasons.…”
Section: Discussionmentioning
confidence: 57%
“…In 1997, Zlotta et al 26 rst used RFA to treat small RCC. The RFA is widely used as an alternative treatment for small RCC due to its advantages of minimal trauma, good e cacy, fast recovery, fewer complications, strong repeatability, low requirements for patient primary conditions, and the ability to be performed under local anesthesia 4,7,27 . However, multiple studies have reported that insu cient intraoperative ablation and the inability to evaluate the ablation effect in real-time by conventional US, CT, or MRI leads to tumor residue and local recurrence after RFA [28][29][30] .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Malignant renal tumors, also known as kidney cancer, have become one of the ten most common cancers in the world in recent years (Jasinski et al 2023). According to statistics, the incidence of kidney cancer has increased from 3% to more than 7% in the past decade.…”
Section: Introductionmentioning
confidence: 99%
“…Among the different thermo-electro-mechanical characteristics of tissues, tissue thermal properties underlie the mechanisms of heat transfer within biological media [ 5 ]. Hence, their accurate estimation is also favorable in view of the increased effectiveness and safety of thermal-energy-based therapies for the treatment of various diseases [ 6 , 7 , 8 , 9 , 10 ]. The thermal properties regulate the processes of conduction, storage, and release of thermal energy within the tissue [ 5 ].…”
Section: Introductionmentioning
confidence: 99%